Exploring the implications of blocking renin-angiotensin-aldosterone system and fibroblast growth factor 23 in early left ventricular hypertrophy without chronic kidney disease - Watanabe, Kentaro; Fujii, Hideki; Okamoto, Kohei; Kono, Keiji; Goto, Shunsuke; Nishi, Shinichi (Frontiers in Endocrinology, 2023)
Whether fibroblast growth factor 23 (FGF23) directly induces cardiac left ventricular hypertrophy (LVH) remains controversial. Recent studies showed an association between FGF23 and the renin-angiotensin-aldosterone system (RAAS). The aim of this study was to investigate changes in FGF23 levels and RAAS parameters and their influences on LVH. In the first experiment, male C57BL/6J mice were divided into sham and transverse aortic constriction (TAC) groups. The TAC group underwent TAC at 8 weeks of age. The mice were sacrificed at 1, 2, 3, and 4 weeks after TAC, and blood and urine samples were obtained. Cardiac expressions of FGF23 and RAAS-related factors were evaluated, and cardiac histological analyses were performed. In the second experiment, the Sham and TAC groups were treated with vehicle, angiotensin-converting enzyme (ACE) inhibitor, or FGF receptor 4 (FGFR4) inhibitor and evaluated in the same way as in the first experiment. In the early stage of LVH without chronic kidney disease, serum FGF23 levels did not change but cardiac FGF23 expression significantly increased along with LVH progression. Moreover, serum aldosterone and cardiac ACE levels were significantly elevated, and cardiac ACE2 levels were significantly decreased. ACE inhibitor did not change serum FGF23 levels but significantly decreased cardiac FGF23 levels with improvements in LVH and RAAS-related factors, while FGFR4 inhibitor did not change the values. Not serum FGF23 but cardiac FGF23 levels and RAAS parameters significantly changed in the early stage of LVH without chronic kidney disease. RAAS blockade might be more crucial than FGF23 blockade for preventing LVH progression in this condition.